The relationship between portfolio diversification strategies and property companies stock price / Saifuliza Omar - Omar, Saifuliza (2007)
This study analyzed the relationship between portfolio diversification strategies of eighteen selected listed property companies on the movement of stock prices for I I-year period from 1996 to 2006. The diversification strategies on long-term trend in stock price are tested using monthly transaction data of property stock. This data obtained from Bursa Malaysia as well as from Data Stream. The dependent variable for this study is property company stock price that is measures its volatility using coefficient of variation and independent variable is the portfolio diversification. The dependent and independent variables are analyzed by using simple regression, and multi-regression. The result shows that there is relationship exists between all independent variable and dependent variable. Meaning that there is a relationship between portfolio diversification strategies and the stock price and the relationship exist is a positive relationship. Positive relationship means, if independent variable increase, the dependent variable will also increase.